Changes of genetic apolipoprotein phenotypes caused by liver transplantation. Implications for apolipoprotein synthesis. - Kraft, H G (1989)
Liver transplantation provides a unique opportunity to investigate the contribution in vivo of the liver to the synthesis and degradation of genetically polymorphic plasma proteins. We have determined the genetic polymorphisms plasma proteins. We have determined the genetic polymorphisms of apo A-IV, apo E, and of the Lp(a) glycoprotein (apo (a] in the plasma of subjects undergoing liver transplantation and in respective organ donors. The results show that in humans, greater than 90% of the plasma apo E and virtually all apo (a) are liver derived, whereas this organ does not significantly contribute to plasma apo A-IV levels.